(3JgPjH GdCSeGA hGddZGJs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3eMeO GHf ehSi s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdeUfhYGJ hHGQi GdHQjGJ heOHQ GdcGFfGJ s
(3BNQgG (B:s
(3ef JQLeI ZjdGf SdeI (B: (3hcGf TGYQkG eMSfkG Jhai BNQ NdGaI YeQHf GdNWGH Je GdLRA GdChd ef cJGH JgPjH GdCSeGA hGddZGJ jJdhg ai GdLRA GdChd ef cJGH JgPjH GdCSeGA hGddZGJ ef jJdhg ai GdLRA GdKGfi Ef TGA Gddg MQa GdaGA (B: (3GdaQGaUI CHh MSGf s
(3GfXQ HQbe (B" 1010 " (3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
Keywords: (3GdJGQjNs